2011
DOI: 10.1016/j.compscitech.2011.02.008
|View full text |Cite
|
Sign up to set email alerts
|

In situ X-ray microtomography characterization of damage in SiCf/SiC minicomposites

Abstract: The purpose of the present study is to characterize matrix crack propagation and fiber breaking occurrences within SiC/SiC minicomposite in order to validate later on a multiscale damage model at the local scale. An in-situ X-ray microtomography tensile test was performed at the European Synchrotron Radiation Facility (ESRF, ID19 beamline) in order to obtain 3-dimensional (3D) images at six successive loading levels. Results reveal a slow and discontinuous propagation of matrix cracks, even after the occurrenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(55 citation statements)
references
References 40 publications
(50 reference statements)
5
47
2
1
Order By: Relevance
“…The degradation mechanisms are in good agreement with results from a recent study conducted at CEA Saclay, emphasizing the dependence of the crack propagation with loading for CVI-SiC f /SiC minicomposites [8]. …”
Section: Discussionsupporting
confidence: 80%
“…The degradation mechanisms are in good agreement with results from a recent study conducted at CEA Saclay, emphasizing the dependence of the crack propagation with loading for CVI-SiC f /SiC minicomposites [8]. …”
Section: Discussionsupporting
confidence: 80%
“…They reported that the damage mechanisms in PA/GF are characterized by matrix plasticization and microcracks, fiber pull out and fracture. X-ray micro-computed tomography (lCT) technique has been used to investigate damage mechanisms in various composite materials [14][15][16][17][18]. Thanks to its inherent 3D analysis capabilities, the damage mechanisms can be identified and quantified in the bulk material, though usually careful data treatments are needed such as to resolve the lower resolution of lCT voxel as compared to the damage size and the presence of artifacts [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Stitched images built from several high resolution images (1 pixel % 0.07 Â 0.07 lm 2 ) are used to get accurate statistical data about fibers and porosity distributions using image analysis. Note that full 3D analyses of the microstructures, based on X-Rays micro-computed tomography (Chateau et al, 2011), have shown that the variations of the pore sections along the fiber direction are small. They are neglected in the present study focused on the influence of the transverse geometry of the tows.…”
Section: Methodsmentioning
confidence: 99%